2019
DOI: 10.1002/chem.201806126
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks and Other Crystalline Materials for Ultrahigh Superprotonic Conductivities of 10−2 S cm−1 or Higher

Abstract: Proton‐conducting materials in the solid state have received immense attention for their role as electrolytes in proton‐exchange membrane fuel cells. Recently, crystalline materials—metal–organic frameworks (MOFs), hydrogen‐bonded organic frameworks (HOFs), covalent organic frameworks (COFs), polyoxometalates (POMs), and porous organic crystals—have become an exciting research topic in the field of proton‐conducting materials. For a better electrolyte, a high proton conductivity on the order of 10−2 S cm−1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 70 publications
2
112
0
Order By: Relevance
“…In water-assisted proton-conducting MOFs, proton transformation relies on guest water molecules, whereas in anhydrous proton-conducting MOFs, proton conduction depends on the existing protons of heterocyclic compounds, organic acids, and inherent water molecules. Therefore, the majority of improvements to proton conductivity involve the introduction of acidic functional groups (e.g., –COOH, –SO 3 H, and –OH) or guest molecules (e.g., H 2 O, imidazole, and triazole) into the MOF network [323] , [324] . With this in mind, we highlight in this section some of the most recent research into proton-conducting MOFs for fuel cell applications.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…In water-assisted proton-conducting MOFs, proton transformation relies on guest water molecules, whereas in anhydrous proton-conducting MOFs, proton conduction depends on the existing protons of heterocyclic compounds, organic acids, and inherent water molecules. Therefore, the majority of improvements to proton conductivity involve the introduction of acidic functional groups (e.g., –COOH, –SO 3 H, and –OH) or guest molecules (e.g., H 2 O, imidazole, and triazole) into the MOF network [323] , [324] . With this in mind, we highlight in this section some of the most recent research into proton-conducting MOFs for fuel cell applications.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…[9][10][11][12][13] Kanda et al first reported ap rotonc onductive MOFs in 1979, [14] and since then, these materials have becomeanew field of research, making significant progress. [15][16][17][18][19][20][21][22][23][24] Unlike semicrystalline or amorphousp olymers, the high crystallinity of MOFs is very suitable for studying protont ransport pathway and the conductionm echanism, demonstrating that protonc an transit through modified groups on the surfaceo ft he cavity (e.g., H 2 O, -SO 3 Ha nd -PO 3 H 2 )a nd guests in the cavity (e.g.,i midazole, histamine and ionic liquids). [5,16,[25][26][27][28] On the other hand, based on the outstanding advantagesofMOFs, the exploration of the practical application of electrically conductive MOFs has received extensive attention, especially in the field of chemoresistive sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Kanda et al. first reported a proton conductive MOFs in 1979, and since then, these materials have become a new field of research, making significant progress . Unlike semicrystalline or amorphous polymers, the high crystallinity of MOFs is very suitable for studying proton transport pathway and the conduction mechanism, demonstrating that proton can transit through modified groups on the surface of the cavity (e.g., H 2 O, ‐SO 3 H and ‐PO 3 H 2 ) and guests in the cavity (e.g., imidazole, histamine and ionic liquids) .…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy of proton conduction was estimated to be 0.33 eV by the least‐squares fitting in the slopes (Figure 3d), which indicates that proton conductivity in POPM mainly follows the Grotthuss mechanism. [ 37,38 ]…”
Section: Figurementioning
confidence: 99%